Artificially low mild cognitive impairment to normal reversion rate in the Alzheimer's Disease Neuroimaging Initiative. Issue 4 (2nd January 2019) - Thomas, Kelsey R.; Eppig, Joel S.; Weigand, Alexandra J.; Edmonds, Emily C.; Wong, Christina G.; Jak, Amy J.; Delano‐Wood, Lisa; Galasko, Douglas R.; Salmon, David P.; Edland, Steven D.; Bondi, Mark W.; ,
Abstract: Introduction: We examined reasons for low mild cognitive impairment (MCI)‐to‐cognitively normal (CN) reversion rates in the Alzheimer's Disease Neuroimaging Initiative (ADNI). Methods: CN and MCI participants were identified as remaining stable, progressing, or reverting at 1‐year of follow‐up (Year 1). Application of ADNI's MCI criteria at Year 1 in addition to Alzheimer's disease biomarkers by group were examined. Results: The MCI‐to‐CN reversion rate was 3.0%. When specific components were examined, 22.5% of stable MCI participants had normal memory performance at Year 1 and their Alzheimer's disease biomarkers were consistent with the stable CN group. At Year 1, when all MCI criteria were not met, the more subjective Clinical Dementia Rating rather than objective memory measure appeared to drive continuation of the MCI diagnosis. Discussion: Results demonstrate an artificially low 1‐year MCI‐to‐CN reversion rate in ADNI‐diagnosed participants. If the Logical Memory cutoffs had been consistently applied, the reversion rate would have been at least 21.8%.